A Genre Analysis on The Discussion Section Of Quantitative And Qualitative Research Articles In ELT And Linguistics - Alfin Zalicha Hilmi; Toyyibah; Nur Afifi (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2021)
This study aimed at: 1) investigating the move and steps found in quantitative and qualitative research articles discussion; 2) investigating the rhetoric structure patterns of quantitative and qualitative research article discussion. This study is a qualitative-research focusing on genre analysis on qualitative and quantitative RA discussions. There were 20 qualitative and 20 quantitative research article discussions of EFL and applied linguistics journals were investigated in this research. Using Yang & Allison’s (2003) framework to analyze the data, it is found that all moves in the framework were employed in RA discussion of both qualitative and quantitative research. However, the number of occurrences of each move were different between discussion section of these two different approaches. Furthermore, the patterns of both qualitative and quantitative RA discussion was not significantly different. There were two types of patterns in RA discussion both in qualitative and quantitative, repetitive pattern and organized pattern. although there were some variations in each of those patterns. The present study provides more evidence of generic structure of RA discussion section as well as proposes some useful insights related to move analysis on research article discussion in ELT and Linguistics area. Limitations and recommendations are discussed in this study.